2018
DOI: 10.1002/phar.2091
|View full text |Cite
|
Sign up to set email alerts
|

Guideline‐Directed Medical Therapy and Survival Following Hospitalization in Patients with Heart Failure

Abstract: Our study suggests that GDMT initiation is associated with increased survival, and discontinuation of therapy is associated with reduced survival in hospitalized patients with HF. Future studies should be conducted to confirm the impact of GDMT therapy modification in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 28 publications
1
51
0
5
Order By: Relevance
“…18 Uptitration of GDMT in patients with heart failure with reduced ejection fraction is associated with a decreased risk of mortality, while discontinuation is associated with an increased risk of mortality. 19 However, recent registry data indicate that intensity of GDMT is just as likely to be decreased as increased during the hospitalization. 20 Nevertheless, predischarge initiation of medications may be associated with higher attained doses in follow-up.…”
Section: During Hospitalizationmentioning
confidence: 99%
“…18 Uptitration of GDMT in patients with heart failure with reduced ejection fraction is associated with a decreased risk of mortality, while discontinuation is associated with an increased risk of mortality. 19 However, recent registry data indicate that intensity of GDMT is just as likely to be decreased as increased during the hospitalization. 20 Nevertheless, predischarge initiation of medications may be associated with higher attained doses in follow-up.…”
Section: During Hospitalizationmentioning
confidence: 99%
“…Эффек тивность депрескрайбинга оценивалась по следующим конечным точкам: первичные -прекращение участия в исследовании, изменение продолжительности физиче ской нагрузки по сравнению с исходным уровнем, вто ричные -ФК по New York Heart Association (NYHA), ка чество жизни, симптомы застойной СН и отказ от тера пии ЛС или плацебо изза ухудшения симптомов СН [10]. Безопасность депрескрайбинга оценивали с помощью электрокардиографии, рентгенографии органов грудной клетки, измерения АД, ЧСС, анализа ряда лабораторных показателей [35].…”
Section: ингибиторы апфunclassified
“…Выводы из анализа имеющихся литературных дан ных по депрескрайбингу ряда ЛС при СНнФВ соответ ствуют данным, опубликованным R. H. Tran с соавт. [35]. Авторы проанализировали результаты 5091 госпитали зации больных, наблюдающихся в рамках исследования ARIC (The Atherosclerosis Risk in Communities).…”
Section: дигоксинunclassified
See 1 more Smart Citation
“…Effectiveness of beta blockers in patients of heart failure with these common co‐morbidities have not been discussed in the guidelines, and their use appears mere extrapolation of the data of the trials. The observational report of heart failure hospitalization in the ARIC cohort showed that, initiation of GDMT reduced mortality at 1 year, but 23% patients needed GDMT modification predicted by selected comorbidities and disease acuity …”
Section: Beta Blockers In Heart Failure Patients With Other Co‐morbidmentioning
confidence: 99%